2019
DOI: 10.1111/ejss.12758
|View full text |Cite
|
Sign up to set email alerts
|

Will heterotrophic soil respiration be more sensitive to warming than autotrophic respiration in subtropical forests?

Abstract: Understanding the responses of heterotrophic (Rh) and autotrophic (Ra) components of soil respiration (Rs) to warming is important in evaluating and modelling the effects of changes in climate on soil carbon (C) cycling in terrestrial ecosystems. We used a mesocosm system with buried heating cables (5°C warming) to investigate the responses of Rs, Rh and Ra to warming in a subtropical forest in southern China. Soil CO2 effluxes were measured with a portable automatic soil CO2 flux system from March 2014 to Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…At present, many studies have shown that future climate change will promote soil heterotrophic respiration [37,38]. The results of this study showed that future climate change under three RCP scenarios had a positive effect on forest soil heterotrophic respiration in arid and humid regions, which is consistent with previous studies.…”
Section: Soil Heterotrophic Respirationsupporting
confidence: 91%
“…At present, many studies have shown that future climate change will promote soil heterotrophic respiration [37,38]. The results of this study showed that future climate change under three RCP scenarios had a positive effect on forest soil heterotrophic respiration in arid and humid regions, which is consistent with previous studies.…”
Section: Soil Heterotrophic Respirationsupporting
confidence: 91%
“…Studies over the past decades have shown that the warming response of microbial respiration is highly variable. Previous studies showed that warming could stimulate microbial respiration due to increased microbial biomass C (Liu et al., 2019), soil nutrient availability (Ali et al., 2018), root exudates (Li et al., 2013), enzymatic activity (Bragazza et al., 2012; Li et al., 2017), or plant production (Euskirchen et al., 2009). Some other studies showed opposite results; that is, microbial respiration inhibited by warming, which resulted from decreased soil water availability (Fang et al., 2018; Liu et al., 2009), labile C (Li et al., 2019), microbial biomass C (Chen, et al., 2016), or enzymatic activity (Garcia‐Palacios et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 40 one-year-old C. lanceolata seedlings were selected from a local nursery; the seedlings were uniform in plant height and basal diameter. The average height and basal diameter of seedlings were 25.7 ± 2.5 cm and 3.4 ± 0.4 mm, respectively [34].…”
Section: Study Site and Experimental Setupmentioning
confidence: 94%
“…The different results demonstrated that seasonal changes significantly affect the antioxidant system [28]. This could be largely related to the significant changes in temperature and precipitation [34]. It has been reported that plants exposed to moisture stress increase antioxidant activities in response to oxidative stress [28].…”
Section: Warming Effects On Reactive Oxygen Species and Antioxidant Ementioning
confidence: 97%
See 1 more Smart Citation